Nocardiosis: a neglected chronic lung disease in Africa?. Issue 11 (November 1988) - Baily, G G; Neill, P; Robertson, V J
Abstract : Nocardia organisms were cultured from the sputum of 11 patients at the central hospitals in Harare, Zimbabwe, over a 12 month period. Pulmonary nocardiosis was diagnosed in one further patient on the basis of direct microscopy. Among the nine patients available for follow up, pulmonary nocardiosis was considered to be the major clinical problem in six. The patients usually presented with a chronic pulmonary infection with fever and cough without evidence of dissemination of underlying systemic disease. The chest radiograph showed consolidation in any part of the lung, and this was seen to extend slowly over several months. Prolonged diagnostic delay was a frequent problem. Haemoptysis, alcohol abuse, and empirical treatment for tuberculosis commonly featured in the history. Treatment with sulphonamides was generally successful in those patients who complied. Nocardiosis is a treatable lung disease that may be more common in developing countries than is currently recognised.